Optimization of poloxamer 188 concentration as media for nanoparticle dispersion: effect of concentration, nanoparticle size and in vitro penetration through blood brain barrier (Funded work) - SITI NORSYAFIKA KAMARUDIN; MINAKETAN TRIPATHY; IGOR IEZHITSA; GABRIELE RUTH ANISAH FROEMMING; RENAD ALYAUTDIN; NAFEEZA MOHD ISMAIL (International Journal of Pharma and Bio Sciences, 2017)
One percent w/v of various surfactants have been used for the dispersion of nano particles in the dispersant media and their size being maintained at nanometer range.While investigating a nanoparticle based project and dispersing PLGA nanoparticles as synthesized based on previous literature with modification in Poloxamer 188 (PLX188) at a concentration of 1% w/v as dispersion media, a massive change in size is observed. Hence a systematic titration study regarding the concentration effect (0.1-4% w/v) of PLX188 on PLGA nanoparticles has been designed using acoustic spectroscopy to study the parameters of size and its distribution. Supporting experiment using dynamic light scattering (DLS) technique-using concentration ranging 0.01% to 0.1% w/v PLX188 has been carried out to compare and validate the trend using different techniques. In this experiment 1% PLGA dispersion system was prepared in water and parameters of size and distribution were measured. Then the system was successively titrated with addition of PLX188 starting from 0.1 to 4% to observe the effect of surfactant concentration on size. The nanoparticle size increased from 27 nm (in case of system without PLX188) to 1.58 μm (in case of 0.1% w/v presence of PLX188) and continued to grow bigger with the increase in PLX188 concentration. DLS results showed similar trend of enlargement in size of the particles even at the presence of 0.01% to 0.1% w/v PLX188 and the morphology further confirmed the findings of the change in size of the PLGA nanoparticles. The size distribution is also affected. The PLGA nanoparticles uptake using of 0.01% w/v PLX188 as dispersion media was a success using Human Brain Microvascular Endothelial Cells (HBMEC) as a blood brain barrier model and hence the above concentration is optimized as the suitable amount of surfactant to be used during the nanoparticles dispersion